Tahap Kesedaran Pekerja Mengenai Keselamatan dan Kesihatan Pekerjaan - Mashitoh, Yakob (2012)
Annual Report 2009 Social Security Organization (SOCSO), reported that the manufacturing sector recorded the highest number of accidents compared to other sectors of industry which is 31.18% from 34.376 cases occurred in 2009. According S.C.Hu (1998) workers, who have limited knowledge and awareness on occupational safety and health, can become a leading cause of occupational injury. Therefore, NAM employee's involved with this research because of NAM included in the manufacturing industry. This study aimed to identify workers' awareness on safety and health (S & H) in the workplace. Research focuses on three types of independent variables that can affect a dependent variable: the dependent variable is the occupational safety and health awareness. Then the three types of independent variables in this study are working environment, employer’s commitment in providing training to employees and the role of OSH committee. Data obtained through questionnaires were distributed. Data is analyzed through the "Windows Statistical Package for Social Science 16" or (SPSS). Descriptive analysis is used to measure the level of employee awareness of OSH by using frequency, min. Meanwhile, regression analysis were use to see the relationship between the three independent variables of the working environment, the role of employers to provide training and role OSH committee the respondents' awareness level of S & H. The results showed that employees has a high level of awareness of the S & H with mean M = 4.36. Working environment is the most influence factor that can give the effect to employee level awareness with a high mean value of M = 4.22. Results from the analysis conducted by multiple regression the working environment has a strong relationship in the relationship with the level of awareness of the high beta (β = 0572, p = 0.000). Finally, this study found that to enhance employee awareness of NAM on the S & H, employer should increase training, increase the awareness campaigns about the S & H, conducts training programs for S & H continuously or periodically, and enforce the use of protection to employees working in high risk areas.